2013
DOI: 10.2105/ajph.2012.300931
|View full text |Cite
|
Sign up to set email alerts
|

Individual, Family Background, and Contextual Explanations of Racial and Ethnic Disparities in Youths’ Exposure to Violence

Abstract: We used data from the Project on Human Development in Chicago Neighborhoods to examine the extent to which individual, family, and contextual factors account for the differential exposure to violence associated with race/ethnicity among youths. Logistic hierarchical item response models on 2344 individuals nested within 80 neighborhoods revealed that the odds of being exposed to violence were 74% and 112% higher for Hispanics and Blacks, respectively, than for Whites. Appreciable portions of the Hispanic-White… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 41 publications
6
131
0
Order By: Relevance
“…Fifth, although the predictive effects of self-control and lifestyles measures were adjusted for several important confounding factors, other domains could also have been considered. Notably, family environment measures other than low parental education, which was included in the current study, could have been incorporated as additional confounding factors (e.g., Zimmerman & Messner, 2013). Thus, we cannot completely rule out the possibility that some associations of the self-control and lifestyle measures to the criterion variables were inflated due to omitted third variables.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Fifth, although the predictive effects of self-control and lifestyles measures were adjusted for several important confounding factors, other domains could also have been considered. Notably, family environment measures other than low parental education, which was included in the current study, could have been incorporated as additional confounding factors (e.g., Zimmerman & Messner, 2013). Thus, we cannot completely rule out the possibility that some associations of the self-control and lifestyle measures to the criterion variables were inflated due to omitted third variables.…”
Section: Discussionmentioning
confidence: 98%
“…It asserts that specific lifestyle characteristics, such as affiliation with deviant peers who can take on the role of potential offenders or co-offenders (e.g., Sampson & Lauritsen, 1990;Schreck et al, 2002), differentially expose Downloaded by [University of Windsor] at 15:54 17 November 2014 individuals to risky situations which increase the risk for both criminal behavior and victimization (Hindelang et al, 1978). Supporting this notion, research consistently has found that individuals who affiliate with deviant peers are at greater risk for offending (e.g., Maldonado-Molina et al, 2010;Wiesner, Capaldi, & Kim, 2012) and victimization (e.g., Gibson, 2012;MaldonadoMolina et al, 2010;Sampson & Lauritsen, 1990;Schreck, Fisher, & Miller, 2004;Schreck et al, 2002;Zimmerman & Messner, 2013). Reasons provided by researchers for why affiliating with deviant peers increases the likelihood of being victimized include that a group of deviant/delinquent individuals has a greater likelihood of preying on each other, as well as being victimized for retaliatory reasons by other deviant groups (Schreck et al, 2002).…”
Section: Background: Self-control and Lifestyle Theoriesmentioning
confidence: 96%
See 3 more Smart Citations